Neuromodulation for Addiction by Transcranial Direct Current Stimulation: Opportunities and Challenges - Bashir, Shahid (Ann Neurosci, 2016)
The field of neuromodulation encompasses a wide spectrum of interventional technologies that modify the pathological activity within the nervous system to achieve a therapeutic effect. Therapy, including transcranial direct current stimulation, has shown promising results across a range of neurological and neuropsychiatric disorders. This article reviews the state-of-the-art of neuromodulation for addiction and discusses the opportunities and challenges available for clinicians and researchers interested in advancing the neuromodulation therapy. A neuromodulation-based approach for addiction has the advantage that the effects might be immediate and selective to the dysfunction. If an alteration in the mechanisms of brain plasticity indeed represents the proximal cause for nicotine-associated cognitive decline and is a critical contributor to the early pathogenesis of addiction, novel interventions that forestall the development of symptoms might be possible.